EFEKTIVITAS KORAN DIGITAL BAGI MAHASISWA JURUSAN ILMUKOMUNIKASI FAKULTAS ILMU SOSIAL DAN POLITIK UNIVERSITAS SAM RATULANGI (Studi pada Harian Tribun Manado) - Poluan, Shencovof; Senduk, Johny; Rondonuwu, Sintje (ACTA DIURNA KOMUNIKASI, 2015)
Effectiveness of Newspaper Digital Communication for Students Department of Social and Political Sciences Faculty of the University of Sam Ratulangi (Study Tribunmanado.co.id). Developments in information technology from conventional to digital media, or more commonly known by the online media, led to intense competition among the businessmen newspaper or print media to maintain the reader's interest and make it easier to get the desired information readers. Tribun Manado stands as one regional newspaper in North Sulawesi to modernize their conventional digital newspaper or online news (tribunmanado.co.id) in order to accelerate and facilitate the presentation of information to the public. North Sulawesi community well-acquainted with the daily news stands Tribun manado because the presentation is weighted, balanced and easy to understand. With the presence of a digital newspaper or online news, the researcher was interested to study the effectiveness of digital newspaper tribunmanado.co.id because most communities north Sulawesi has not been too understand and know about digital newspapers or online media. The reason why the researchers chose the students because students are users of online media is very active but unfortunately rarely use the print media as a means of information. Researchers focused on students from the Department of Communications Faculty of Social and Political Science University of Sam Ratulangi, because researchers assume they already understand and know about the presence of a digital newspaper or online news. Based on the analysis of the interview data, we concluded that the presence of a digital newspaper tribunmanado.co.id effective enough for the students internet users as their source of information. Practicality and efficiency of a given Internet service, tends to lead to the recognition of a student on the ease of access to digital newspapers or online news tribunmanado.co.id.